2005
DOI: 10.2166/wst.2005.0532
|View full text |Cite
|
Sign up to set email alerts
|

Performance of UASB septic tank for treatment of concentrated black water within DESAR concept

Abstract: Separation of wastewater streams produced in households according to their origin, degree of pollution and affinity to a specific treatment constitutes a starting point in the DESAR concept (decentralised sanitation and reuse). Concentrated black water and kitchen waste carry the highest load of organic matter and nutrients from all waste(water)streams generated from different human activities. Anaerobic digestion of concentrated black water is a core technology in the DESAR concept. The applicability of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 2 publications
8
43
1
3
Order By: Relevance
“…Lower H 2 S values in the MEC-septic tank were measured between day 25 to day 60 of phase 1 and during phase 2, they became below detection limits (<2 ppmv). The H 2 S concentrations in the control reactor were as high as 700 ppmv (day [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and on average about 200 ppmv (day 20-98). …”
Section: Biogas Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower H 2 S values in the MEC-septic tank were measured between day 25 to day 60 of phase 1 and during phase 2, they became below detection limits (<2 ppmv). The H 2 S concentrations in the control reactor were as high as 700 ppmv (day [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and on average about 200 ppmv (day 20-98). …”
Section: Biogas Compositionmentioning
confidence: 99%
“…The combination of an Upflow Anaerobic Sludge Blanket and a septic tank (UASB-septic tank) enhances the contact between the sludge bed and the sewage, increases the removal of suspended solids and allows methanation of dissolved organic compounds [7]. In the context of source separated decentralized water treatment, the UASB-septic tank has been proposed for the treatment of black water as well [6][7][8]. Black water (mainly faeces and urine) has high concentrations of organic material and nutrients, making it a suitable input for anaerobic digestion.…”
Section: Introductionmentioning
confidence: 99%
“…is excreted and it is assumed that around 80% of the COD ends up in the concentrated line for anaerobic digestion, mainly by the advanced concentration step and with a minor sludge contribution from subsequent biological treatment. f Anaerobic digestion of primary and secondary sludge at 35°C converts around 50% of the COD into biogas (Wett et al, 2007;Siegrist et al, 2008), whereas digestion of black water and kitchen waste can remove up to 70-80% of the COD, even at 25°C (Kujawa-Roeleveld et al, 2005;Meulman et al, 2010), which is in the same order as the digestability of (flocculated) grey water (Elmitwalli and Otterpohl, 2007;Hernandez Leal et al, 2010). A 70% COD conversion from mixed sources was therefore assumed to be feasible at 35°C.…”
Section: Sewage As a Resource: Why Not?mentioning
confidence: 99%
“…Anaerobic treatment is regarded as the core technology for energy and nutrient recovery from source separated domestic wastewater (Otterpohl et al, 1999;Kujawa-Roeleveld and Zeeman, 2006). Previous research showed that concentrated black water (faeces and urine collected in a vacuum toilet) can be efficiently treated in a UASB (Upflow anaerobic sludge blanket) reactor at a relatively short hydraulic retention time (HRT) of 9.1 days (de Graaff et al, 2010), in a UASB septic tank at a longer HRT of 29 days (Kujawa-Roeleveld et al, 2005) or in a CSTR at an HRT of 20 days (Wendland et al, 2007). A methane production of 1.8 m 3 CH 4 per m 3 of black water can be achieved, which can be converted to 56 MJ/p/y as electricity and 84 MJ/p/y as heat by combined heat and power (CHP) (de Graaff et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…95% was conserved in the effluent. However, for more concentrated black water, collected with vacuum toilets (1L per flush), 40% of the phosphorus was removed when applying UASB-septic tank (Kujawa-Roeleveld et al, 2005). …”
mentioning
confidence: 99%